Influence of Submerged Entry Nozzles on Fluid Flow, Slag Entrainment, and Solidification in Slab Continuous Casting - Xingang Zhen; Shiheng Peng; Jiongming Zhang (Metals, 2024)
In this paper, the fluid flow, slag entrainment and solidification process in a slab mold were studied using physical modeling and numerical simulation. The effect of two types of submerged entry nozzles (SENs) was also studied. The results showed that the surface velocity for type A SEN was larger than that using type B SEN. For type A SEN, the maximum surface velocity was 0.63 m/s and 0.56 m/s, and it was 0.20 m/s and 0.18 m/s for type B SEN. The larger shear effect on the top surface made the slag at narrow face impacted to the vicinity of 1/4 wide face, while the slag layer at the top surface was relatively stable for type B SEN. Increasing the immersion depth of SEN decreased the surface velocity and slag entrainment. For type A SEN, the thickness of the solidified shell at the narrow face of the mold outlet was thin (12.3 mm) and there was a risk of breakout. For type B SEN, the liquid steel with high temperature would flow to the meniscus and it was beneficial to the melting of the mold flux. The thickness of the solidified shell at the narrow face of the mold outlet was increased. Furthermore, the surface velocity was also increased and it was not recommended for high casting speed.